Subversion of Literary Conventions in John Irving’s Novels The World According To Garp and Last Night in Twisted River (American & British Studies Annual, 2011)
John Irving is a prominent American storyteller whose plot-driven novels are full of memorable characters. Despite his influences from Victorian novelists, his narratives are unconventional and complex, with various discourses intertwined. Irving’s novels, The World According to Garp and Last Night in Twisted River contain absurd "flat" characters and grotesque incidents. Violence, death and humour are dominant in The World According to Garp. Powerful depictions of the main character, Danny, and the way his imaginative world works parallels the "real" story (Irving’s fictional story). By incorporating into his stories various popular genres such as detective story Irving transgresses the boundary between high and low art, and through metafictional techniques he, as Patricia Waugh would put it, “lays bare the conventions of realistic techniques.”
Keywords: metafiction; framing devices; violence; death; postmodern; John Irving; The World According to Garp; Last Night in Twisted River